1481. Clinical Outcomes of Escherichia coli Infections in Cystic Fibrosis (CF) Patients. (26th November 2018) - Edwards, Brett; Greysson-Wong, Jasper; Somayaji, Ranjani; Waddell, Barbara; Storey, Doug; Surette, Michael; Rabin, Harvey; Parkins, Michael
Abstract: Background: Despite a growing interest in emerging pathogens in CF, research has largely overlooked commonplace organisms. Escherichia coli has been reported in up to 50% of CF respiratory samples, yet little is known about its clinical impact. We sought to investigate outcomes of E. coli infection in CF. Methods: We undertook a retrospective cohort study of patients (≥18 years) attending a Canadian CF clinic between 1978 and 2016 with at least one E. coli positive sputum culture. Infection was classified as transient (≥1 isolate) or persistent (≥3 isolates over a period ≥6 months). Clinical and demographic data were collected from patient charts 2 years pre- and post-incident infection. For each patient with persistent infection, we collected data on two age (±3 years), sex, and time-matched control patients for comparison. Outcomes sought included risk of pulmonary exacerbation (PEx), lung function decline (FEV1 ), antibiotic days, and progression to transplant or death. Susceptibility testing was performed as per CLSI standards. Results: A total of 45 (12.3%) patients (median age 23.5 (IQR 20.0–34.8), 52% male) cultured E. coli in their sputum at least once. At incident infection, 24% had PEx but this was not increased relative to prior visits (RR 0.9, P = 1.00). Of the cohort, 18 (40%) developed persistent infection. Persistent infection developed in patients with lower nutritional scores (BMI) (−2.6 kg/m 2, P < 0.001) and lung function (FEV1 %; 57.2 vs. 74.2, P = 0.02). Compared with matched controls, those with persistent infection had no increase in mean annual lung function decline (difference −1.06%/year, P = 0.24), odds of PEx (OR 1.4, P = 0.26), or mean annual hospital IV days (difference: 0.31 days, 95% CI −4.97 to 5.59 days, P = 0.91). Five patients underwent lung transplantation and three died at 5-year follow-up, but this did not differ between transient and persistent infection ( P = 0.63 and P = 0.25, respectively). TMP-SMX resistance ( P = 0.05), but not ESBL production in incident isolates, was predictive of persistence ( P = 0.56). Conclusion: In this Canadian CF cohort, E. coli infection was common and occurred more frequently in patients with compromised nutrition and lung function. Persistent infection with E. coli did not portend worse clinical outcomes. Multi-centre studies are merited to further understand the epidemiology and clinical impact of E. coli infection. Disclosures: All authors: No reported disclosures.